Selected skin diseases of the feet - Wiktoria Chodun; Kinga Ruszel; Robert Dubel; Barbara Nieradko-Iwanicka (Kazimierz Wielki University, 2021)
Foot skin diseases are common problems encountered by dermatologists. They involve the skin and nails. In addition to the health aspect, there is also an aesthetic aspect, especially troublesome in the summer. It is recommended to visit a dermatologist with any disturbing skin lesion. The article presents an overview of the most common diseases in dermatology and podiatry offices.